Attitudes of pregnant women and mothers of children with orofacial clefts toward prenatal diagnosis of nonsyndromic orofacial clefts in a semiurban set-up in India - Poornima Kadagad; Pascal Pinto; Rajesh Powar (Indian Journal of Plastic Surgery)
Objectives: To assess the attitudes of pregnant women and mothers of children with orofacial clefts toward prenatal diagnosis of clefts and elective termination of pregnancy, and to investigate their opinion about who makes reproductive decisions in the family. Design: Two hundred subjects were included in the study prospectively regarding hypothetical prenatal ultrasound diagnosis of clefts. Setting: The study was done in a private tertiary care institution and a teaching hospital. Subjects/Participants: One hundred pregnant women consulting the Obstetrics department and 100 mothers of children with orofacial clefts in the Cleft and Craniofacial Unit were selected. Materials and Methods: Group I subjects were interviewed using a questionnaire and were shown preoperative and postoperative pictures of children treated for cleft lip and palate. Group II subjects were interviewed using a questionnaire. Results: Only 3% of Group I subjects and 2% of Group II opined that they would choose the elective termination of pregnancy if the fetus was diagnosed with a cleft on an ultrasound scan. In Group II, 70% subjects wished to have known about pregnancy affected with cleft prenatally and 96% said they would definitely avail ultrasound scans to determine pregnancy affected by clefts in future. Conclusions: Majority of the respondents from both the groups chose to continue with the pregnancy affected with a cleft when questioned regarding hypothetical prenatal ultrasound diagnosis of the cleft.